2010
DOI: 10.1186/1476-4598-9-133
|View full text |Cite
|
Sign up to set email alerts
|

Knock down of HIF-1α in glioma cells reduces migration in vitro and invasion in vivo and impairs their ability to form tumor spheres

Abstract: BackgroundGlioblastoma (GBM) is the most common and malignant primary intracranial human neoplasm. GBMs are characterized by the presence of extensive areas of necrosis and hypoxia. Hypoxia and its master regulator, hypoxia inducible factor 1 (HIF-1) play a key role in glioma invasion.ResultsTo further elucidate the functional role of HIF-1α in glioma cell migration in vitro and in invasion in vivo, we used a shRNA approach to knock down HIF-1α expression complemented with genome-wide expression profiling, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
125
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 48 publications
10
125
0
Order By: Relevance
“…27,30 The data from our and other group also showed that HIF-1a enhances the self-renewal activity of CD133-positive glioblastoma cells and inhibits the induction of GSC differentiation. 8,31,32 These data suggest that the mechanism involved in hypoxia-mediated maintenance of GSC maybe cell type specific. Besides, different hypoxic condition may also cause different response.…”
Section: Discussionmentioning
confidence: 87%
“…27,30 The data from our and other group also showed that HIF-1a enhances the self-renewal activity of CD133-positive glioblastoma cells and inhibits the induction of GSC differentiation. 8,31,32 These data suggest that the mechanism involved in hypoxia-mediated maintenance of GSC maybe cell type specific. Besides, different hypoxic condition may also cause different response.…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, hypoxiamimetic agent CoCl 2 has previously been demonstrated that it has potential in modulating the invasive ability of primary and metastatic breast cancer cells (Fu et al, 2009). Knockdown HIF-1α by siRNA inhibiting cell migration and invasion under hypoxic environment was determined in malignant gliomas (Mendez et al, 2010). BNIP3 supports melanoma cell migration and vasculogenic mimicry by orchestrating the actin cytoskeleton (Agostinis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, the inserts were fixed and stained and the number of migrating cells was counted as described. 22 Each assay was performed in duplicate and repeated twice. The data from at least three independent experiments were pooled for statistical analysis.…”
Section: Migration Assaymentioning
confidence: 99%